The Rationality Hypothesis: Help or Hindrance? - Kurt W. Rothschild (Intervention. Zeitschrift fuer Ökonomie / Journal of Economics, 2005)
First paragraph: The assumption of rational decision-making, the maximising or optimising homo oeconomicus, belongs to the fundamental elements of the neoclassical mainstream. It is also an element that has been hotly attacked and defended for a long time without a convincing victory for one side or the other. The following considerations – though none of them is completely new – should help to show why such a one-sided victory is neither likely nor desirable.
Keywords: 330